Exploring Student Engagement in English Learning through Interactive Web Quizzes at Indonesian Schools in Kuala Lumpur - Kirani, Dian Sukmawati; Islam, Muhammad Hifdil; Zainuddin (Universitas Cokroaminoto Palopo, 2026)
This study examines the contribution of interactive web quizzes to student engagement in English language learning at Sekolah Indonesia Kuala Lumpur (SIKL). Using a descriptive qualitative case study design, data were collected through six classroom observations, interviews with one teacher and eight students, and documentation. The findings reveal three dimensions of engagement: behavioral (32 coded excerpts), emotional (28 excerpts), and cognitive (24 excerpts). Behavioral engagement emerged as the most dominant, indicated by increased participation and attentiveness during quiz-based activities. Emotional engagement was reflected in students’ motivation and enjoyment, while cognitive engagement was demonstrated through reflective thinking and attention to feedback. Overall, the results suggest that interactive web quizzes can support active and meaningful learning, although minor challenges such as time pressure and competitive elements were identified. These findings highlight the potential of digital quizzes as an inclusive and engaging instructional strategy in multicultural EFL classrooms.